Zero Emission Mobility Systems in Cities. Inductive Recharge System Planning in Urban Areas - Maternini, Giulio; Riccardi, Stefano; Cadei, Margherita (TeMA - Journal of Land Use, Mobility and Environment, 2014)
In the last few years, “Sustainable” and “Smart” mobility became concepts of fundamental importance and led national government to adopt programmes and measures aimed at reducing the carbon emissions of private and commercial vehicles. The final goal is to pursue the EU objectives of reducing the greenhouse gases emission in transportation sector. The progressive electrification of the circulating vehicles represents a possible solution to the air pollution relating problems. A recent innovative research field, which could significantly contribute to the diffusion of the electric vehicles, consists of the inductive recharge systems for electric vehicles. This technology could also bring to considerably environmental and logistic advantages, especially in urban areas. Starting from the analysis of the main ongoing experimentations of these innovative systems in the world, the present paper proposes a possible application of the inductive recharge technology to the public transport vehicles, through the presentation of the case study of Brescia.